Efektivitas Pembangunan Saluran Drainase di Kelurahan Simbangkulon Dalam Mengatasi Banjir - Husna, Arinal; Hermawan Adinugraha, Hendri (JURNAL LITBANG KOTA PEKALONGAN, 2025)
Flooding is a natural disaster that often occurs in several regions in Indonesia, including Pekalongan Regency. One of the areas frequently hit by flooding is Simbang Kulon Village, which is caused by the poor drainage system draining the water flow. The development of drainage infrastructure in this area is an important step in overcoming the problem of recurrent flooding. This research aims to assess the effectiveness of drainage channel infrastructure development in Simbang Kulon Village, especially in Simbang Kulon Gang 2, RW 04. The research method used is a qualitative method with a literature study approach. Secondary data was obtained from literature and previous research, while primary data was obtained through direct observation and interviews. The analysis was carried out by studying the studies of data sources to produce actual conclusions on the research topic. The results showed that the development of drainage channel infrastructure in Simbang Kulon Village has had a significant impact in reducing the intensity of flooding that often occurs. However, the phenomenon of groundwater puddles appearing inside residents' houses during heavy rains is still a challenge that needs to be addressed further. The lack of water catchment areas is one of the main causes of this phenomenon.